2022
DOI: 10.3390/math10152685
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Green Innovation and Corporate Social Responsibility on the Link between Transformational Leadership and Performance: An Examination Using SEM Analysis

Abstract: Since the inauguration of the United Nations Sustainable Development Goals (UNSDGs), environmental performance and sustainability have become more important to decision makers, scientists and leaders of organizations than before. In response to this, leaders of different organizations spend all endeavors conserving resources and ensuring environmental sustainability. In this context, transformational leaders have the capacity to ensure the green performance of their organization. The purpose of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 84 publications
2
9
0
Order By: Relevance
“…My findings were affected to some extent by the effects of the Coronavirus pandemic on the companies and the increase in awareness among various parties of the need to raise awareness of future risks. My findings corroborate with those found by Sobaih et al ( 2022 ) in Saudi context by using a green innovation and CSR as mediating variables to prove the effect of sustainability on corporate performance. The same affirmation on SMEs companies in Saudi Arabia is argued by Al Doghan et al ( 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…My findings were affected to some extent by the effects of the Coronavirus pandemic on the companies and the increase in awareness among various parties of the need to raise awareness of future risks. My findings corroborate with those found by Sobaih et al ( 2022 ) in Saudi context by using a green innovation and CSR as mediating variables to prove the effect of sustainability on corporate performance. The same affirmation on SMEs companies in Saudi Arabia is argued by Al Doghan et al ( 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…Transformational leadership encourages employees' awareness of the importance and meaning of their work, fosters work creativity, and encourages them to realize organizational goals. In line with previous research, for example, the studies of Sobaih, Gharbi, Hasanein, and Elnasr (2022) and Tosun, Parvez, Bilim, and Yu (2022), transformational leadership inspires and motivates employees to achieve high performance and long-term organizational goals by outlining a clear and inspiring vision for the future as well as providing various necessary support resources.…”
Section: Resultssupporting
confidence: 63%
“…This is because studies in the past have shown that transformational leadership is a key factor in the work environment that determines and promotes creativity among the individuals (Mittal and Dhar, 2015). GTL refers to a leadership structure where leader guide employees by inspiring and motivating its employees towards the accomplishment of the organization's environmental vision (Sobaih et al, 2022). According to Chen et al (2014), GTL is described as the leader's behaviour that is intended to give employees a clear vision, support, inspiration and motivation as well as to meet their developmental needs.…”
Section: Theoretical Background and Hypotheses Formulationmentioning
confidence: 99%